Nano-cockle shell powder and alginate as novel injectable bone filler: a preliminary formulation and characterization study - George, Penny; Abdul Hamid, Zariyantey; Abu Bakar, Md Zuki; Bharatham, B. Hemabarathy (Biome Scientia, 2024)
Cockle shells of the Anadara granosa species consist of 95-99% aragonite form of calcium carbonate (CaCO3) crystals. Aragonites are known to be denser which allows it to be incorporated, resolved and replaced by bone tissues over time when used in bone tissue grafting. An injectable biomaterial-based bone filler with appropriate injectability and biological properties was formulated using powdered cockle shells in nanoscale (nCSP) and sodium alginate (Alg). Initial attempts in formulating the bone filler using alginate and citric acid as a setting agent in the composition of nCSP: Alg of 60: 40, 70: 30 and 80: 20 wt.% produced variable results in the bone filler characterization. Characterization study of nCSP-Alg bone filler with 70:30 wt.% compositions showed excellent injectability (p<0.05), viscosity (p<0.05) and anti-washout ability that was further evaluated through physicochemical analysis, morphology and biocompatibility studies. Scanning electron micrographs revealed plate-like nanocrystal deposits with micropores ranging between 1.5 – 7.4 μm. XRD and FTIR evaluation indicated the presences of peaks associated with aragonite form of CaCO3. Biocompatibility studies with MG63 osteoblast showed osteoconductivity of the bone fillers with excellent cell adherence, growth and subsequent mineralization of the matrices. In conclusion, nCSP-Alg biomaterial-based bone filler with 70:30 wt.% compositions shows promising use as a cost effective bone grafting material for clinical application in the field of bone tissue engineering.